Coordination of entrepreneurial growth methods and business retention and expansion outreach. Issue 2 (15th March 2017) - Warren, Will
Abstract: Through a process to conduct a Regional Economic Competitiveness Strategy (RECS) in 2013, Northeast Ohio's business, civic, and philanthropic leaders learned that Northeast Ohio was underperforming the US over the last two decades. The process identified that 65% of jobs created by the regional network annually were tied to business retention and expansion (BRE) efforts, making BRE a core pillar of the RECS. JumpStart Inc. of Northeast Ohio's BRE network was tasked with conducting an analysis of the current BRE system. The experience and entrepreneurial mission of the organization gave JumpStart Inc. a unique perspective on BRE. The analysis brought an entrepreneurial, data-driven process to the BRE system in Northeast Ohio. The process focused on added value through data-driven techniques in targeting of companies; the enhancement of business intelligence capabilities by utilizing entrepreneurial techniques; and leveraging regional assets as a result of greater analysis of company feedback and industry trends.